Antithrombotic/Antiplatelet Treatment in Transcatheter Structural Cardiac Interventions—PFO/ASD/LAA Occluder and Interatrial Shunt Devices - Olasinska-Wisniewska, Anna; Grygier, Marek (Frontiers in Cardiovascular Medicine, 2019)
Transcatheter interventions enable safe and efficient treatment of various structural heart diseases. However, therapy does not finished with the end of the procedure. Device thrombosis is a possible serious complication. Therefore, careful patient management should include optimal antiplatelet or antithrombotic medication to enhance safe and complete endothelial coverage of the implanted device. In case of thrombus formation careful diagnostic evaluation and prompt treatment is crucial. This paper provides an update to current knowledge and understanding of prevention and management of device related thrombosis.